A objetivação do controle de constitucionalidade difuso e a dinâmica constitucional : a permanência da atuação do senado federal com controle de constitucionalidade - Amorim Júnior, José Adrice Paz de (2013)
The changes in society reflect the mode of perception of Constitutional Law and the form of adjudication. Some of these changes require formal amendments of the Constitution, others modify the standard without modifying the text. This occurs through the process of constitutional mutation. The control of constitutionality does not escape the effects of the mutation, allowing, in the case of Brazil, the emergence of a complex control system, adding to the classic forms new possibilities, allowing also the participation of various entities in constitutional interpretation. However, these new changes were not able to overcome the significant role of the Senate in control of constitutionality, and this is due to the recognition of democratic values ​​present in the Brazilian state.